Mementos from Boots multisensory boxes: qualitative evaluation of an intervention for people with dementia: innovative practice - Griffiths, Sarah; Dening, Tom; Beer, Charlotte; Tischler, Victoria (SAGE, 2016)
This qualitative study explored a multisensory (including olfactory) intervention for people with dementia. Six themed boxes (e.g. Childhood) containing items chosen from the Boots archive designed to encourage conversation were used in weekly group sessions. Session participants were people with dementia and care staff from a local care home, a trained facilitator and archivists from Boots UK. Semi-structured interviews explored participants’ experiences of the sessions. Interviews were analysed using Thematic Analysis. The three major themes Engagement (subthemes: Inclusiveness; Emotional involvement; Factors that supported engagement), What’s in the box (subthemes: Contents stimulate memories; Mystery, variety and age of items; Value of olfactory stimuli), and A conversation starter (subtheme: Opportunity for self-expression) reveal the success of the intervention and the value of olfactory stimuli. Multisensory boxes including olfactory stimulation can be an engaging intervention with scope to refine it for people with dementia and their carers in the wider community.